Impacts of official development assistance (ODA) on basic living conditions in Madagascar - NY AINA IANJATINA, Andrianony (KDI School, 2022)
Madagascar is classed among the poorest country in the world, ranked 208th out of 213 countries in terms of GDP per capita. The country is classed in the low-income category with a GDP per capita of 495.49 US dollar in 2020. It is estimated that 75% of people in Madagascar live on less than $1.90 per day. The country is weak and fragile in responding to economic, social or political shocks; that is the reason why external assistance is principally needed. In this context, this study conducts in-depth analysis on this area, to present the effects of external assistance (ODA) on basic living conditions of the population in terms of income, education, health and infrastructures. The results indicate a positive relationship between Oda and Income, Education and Infrastructures; nonetheless, there is a negative relationship between Oda and Crude Death Rate, controlling for main changes years in the data.
Thesis(Master) -- KDI School: Master of Public Management, 2022
Keywords: Economic assistance--Madagascar